Pengaruh Inovasi Produk, Cita Rasa dan Harga Terhadap Peningkatan Pendapatan Usaha Kuliner di Alam Barajo Jambi - Fannydya SalsabilaMaharany; Putri ApriaNingsih; Muthmainnah Muthmainnah (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2026)
The problem in this research is motivated by a phenomenon occurring in culinary businesses in Alam Barajo, Jambi, where product innovation, taste, and price are factors that influence revenue growth. The strategies implemented by culinary entrepreneurs play a significant role in influencing revenue growth. However, in reality, not all strategies implemented produce the desired results. The purpose of this study is to determine the extent to which product innovation, taste, and price influence revenue growth in culinary businesses in Alam Barajo, Jambi. This research is quantitative. The sample used in this study was 92 respondents. The sampling technique used the Slovin formula, and the data sources were primary and secondary data. Data collection techniques used were questionnaires, interviews, and documentation. The data analysis used was validity testing, reliability testing, classical assumption testing (normality, heteroscedasticity, and heteroscedasticity), multiple linear regression analysis, and The problem addressed in this study is motivated by a phenomenon occurring among culinary businesses in Alam Barajo District, Jambi City, where product innovation, taste, and price are considered factors that may influence revenue growth. The strategies implemented by culinary business owners play an important role in increasing business revenue. However, in practice, not all strategies produce the expected outcomes. This study aims to examine the influence of product innovation, taste, and price on revenue growth among culinary businesses in Alam Barajo District, Jambi City. This research employed a quantitative approach. The sample consisted of 92 respondents selected using the Slovin formula. The data sources included primary and secondary data. Data were collected through questionnaires, interviews, and documentation. Data analysis techniques included validity and reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity), multiple linear regression analysis, and hypothesis testing using the t-test, F-test, and coefficient of determination (R²), with the assistance of SPSS version 23. The results indicate that, partially, product innovation does not have a significant effect on revenue growth, whereas taste and price have significant effects on revenue growth. Simultaneously, product innovation, taste, and price have a significant effect on revenue growth. The coefficient of determination (R²) of 79.8% indicates that variations in revenue growth can be explained by product innovation, taste, and price, while the remaining 20.2% is influenced by other factors not examined in this study. hypothesis testing (t-test, f-test, and coefficient of determination) using SPSS version 23. The results of this study indicate that product innovation has no partial effect on revenue increase, taste does, and price does. Simultaneously, product innovation, taste, and price influence revenue increase. The coefficient of determination value of 79.8% indicates that product innovation, taste, and price explain 79.8% of the revenue increase. The remaining 20.2% is influenced or explained by other factors not discussed in this study.